THE INFLUENCE OF AN EXERCISE AND COORDINATION TOWARD THE DRIVE TECHNIQUE FOR BEGINNER TENNIS ATHLETE - Awan Hariono (Jorpres (Jurnal Olahraga Prestasi), 2016)
The aims of this research are to find out: (1) the influence of the difference between the direct practice methods and indirect exercise methods toward the drive technique for beginner tennis athlete; (2) the difference of the influence of high and low coordination skills toward the drive technique of beginner tennis athlete; and (3) the interaction between the exercise method and coordination toward the drive technique of beginner tennis athlete.The research sample was 40 students of Coaching Education Department of Sport Science Faculty of Yogyakarta State University who take field tennis lesson. The technique for taking the sample was done by purposive sampling. There were two variables in this research: (1) manipulative variable which consist of direct exercise methods and indirect exercise methods and (2) attributive variable which consist of sample group who have high and low coordination skill. The dependent variable was tennis field drive skill. The data collected were (1) drive technique data, and (2) eye-arm coordination data. The technique of data analysis was used Variant Analysis (ANA VA) in the level of significance 0.05 and continued by Tukkey test.The result were as follows: (1) there is no difference influence between the direct exercise methods and indirect exercise methods toward the drive technique for new tennis othlete F0  : 0.091 F1 0.05: 4.08; (2) there was a difference of the influence between the group sample who has a high and low coordination skill toward the drive technique for new tennis athlete, Fa: 67.354 Fw.as: 4.08; (3) there was an interaction between coaching and coordinating methods toward the drive technique for new tennis athlete, Fa: 10.030 F1 0.05: 4.08; (3.a) drive technique of the group sample who have high coordination skill by using indirect practice methods gave better influence than by using direct practice methods, qa: 5.1 q1 : 3.9698; (3.b) drive technique of the group sample who have low coordination skill by using direct exercise methods gave better influence that by using indirect exercise methods, q0 : 4.2 q1 o.as: 3.9698. Keywords: exercise methods, coordination, drive technique, and beginner tennis athlete